Letter from the Editor - Bakardjieva , Maria (The Motley Undergraduate Journal, 2023)
The Motley has arrived! Let us welcome it as a peer, a friend, a colleague and a liberator! Why liberator? Because it comes to liberate the best academic work that our undergraduate students do from the obscurity of professors’ drawers and hard drives, from the secretive passwords of university servers. It comes to bring that work out into the light of day. Yes, there are personal blogs and social media platforms where students could have published their papers before, but the Motley is different. Papers appearing in it have passed muster, and a tough one for that matter. It is not the “likes” of like-minded friends that raise these papers to the top of visibility. It is the vetting performed by people who may agree or disagree with each other, peers and professors alike, and where knowledge, talent and good argument win the day. That is why the Motley is the opposite of an echo chamber. It is after all a motley of topics, views and forms of expression, all of which have only one thing in common – the high standards of quality that they have met. In our present day of fake news, false theorizing, and vacuous influencing, we have learned how important it is to have a steady intellectual anchor like that. The liberatory mission of the Motley includes taking down the walls that conceal from the eyes of the community what we learn, create and discuss in our classrooms. It will showcase the gems of original analysis and creativity that our undergrads produce. Where else will your grandma get the chance to revel in your brilliant argument illuminating the major communication and cultural issues of society? How else will your future boss learn about your superior powers as analyst, artist and wordsmith? And maybe, just maybe, your opinionated neighbour or your younger cousin will come to understand some of those complex issues in a new way. While opening our academic spaces to the outside world, the Motley will also work to bring us, their inhabitants, closer to each other. It will reveal what we collectively value, what we find important and for which we strive. It will compel us to work together – as it already has – by creatively combining the efforts of undergraduate and graduate students, faculty, club leaders, librarians, administrators… It will be our collaborative effort, our joint achievement, and our shared pride and joy. We are in it together and we all have a stake to keep it bright, honest, fair and vibrant. The Motley is marching into the limelight today in shining colour thanks to the tireless work that numerous champions and supporters performed on the backstage for months. Starting a project like this from scratch takes faith, dedication and perseverance. The authors, reviewers and editors of this first issue did not have an established publication outlet to hang their labour and hopes on. They had to take a bold step over the gorge that separates an idea from its realization. And they did a gorgeous job at that! The Motley knows it was all these contributors who breathed life into it, and it is their example that will inspire and instruct others down the road. Of all those to whom the Motley will remain forever grateful, one name should be flashed across its first page – Melissa Morris. As its first managing editor, Melissa managed the Motley Undergraduate Journal into existence. She brought together people and computer systems, navigated publication formats and citation styles, wooed, nudged and nagged. She convinced all of us that the Motley was possible, and sure enough, it is here – to stay. Now, it is your turn, the Motley’s first readers. The Motley team expects you to do your job diligently and devotedly. Read, view, discuss, criticize! Then come and join us as authors, reviewers and editors - a motley of powers, all in your hands!